Evaluasi Efektivitas Penggunaan Teknologi Pembelajaran Interaktif dalam Mata Pelajaran Matematika di Sekolah Dasar - Setra, Lajuardi; Sopian, Asep (Papanda Publisher, 2022)
The aim of this study was to evaluate the effectiveness of using interactive learning technology to enhance students' understanding in mathematics at SDN Genteng 1 elementary school. Employing a quantitative approach and an experimental research design, two groups of students (30 students per group) were involved in this study: an experimental group receiving instruction with interactive technology, and a control group receiving conventional instruction. Data were collected through pre-tests and post-tests as well as observation of student interaction with the interactive technology during the learning period. The results indicated that students in the experimental group experienced a significant improvement in understanding compared to the control group. The average post-test scores for the experimental group showed a greater increase compared to the control group. Thus, the use of interactive learning technology proved to be effective in enhancing students' understanding in mathematics at the elementary school level. This finding underscores the importance of integrating technology in education to create engaging and effective learning environments. Therefore, it is recommended that instructional approaches integrating interactive technology continue to be developed and implemented in teaching practices. Further steps are necessary to deepen understanding of how interactive technology can be effectively integrated into education and to identify the best strategies for optimizing its benefits for student learning outcomes. This abstract provides a comprehensive overview of the research findings and their implications for educational practice.